Elevated mir‐141 in obesity: Insights into the interplay with sirtuin 1 and non‐alcoholic fatty liver disease - Nikta Dadkhah Nikroo; Habib Jafarinejad; Zeynab Yousefi; Zohreh Abdolvahabi; Mojtaba Malek; Pejman Mortazavi; Abdolreza Pazouki; Somayeh Mokhber; Mitra Nourbakhsh (Wiley, 2024)
Abstract Background Changes in gene expression related to obesity are linked to microRNAs, such as miR‐141, which play a crucial role in metabolic homeostasis. Sirtuin 1 (SIRT1), an enzyme that plays a crucial role in regulating various cellular functions and metabolism, is implicated in obesity and the ensuing non‐alcoholic fatty liver disease (NAFLD). The aim of this research was to evaluate the levels of miR‐141 and its relationship with SIRT1 and NAFLD. Methods A group of 100 adults (50 with obesity and 50 with normal‐weight) were selected and underwent complete clinical evaluation and anthropometric measurements. Biochemical parameters were assessed in blood serum, and the levels of miR‐141 in plasma were measured by real‐time PCR. The expression of the SIRT1 gene was also evaluated in the peripheral blood mononuclear cells using Real‐time PCR. The ELISA technique was used to determine insulin levels. Liver steatosis was assessed by ultrasound. Results The results showed that levels of miR‐141 were significantly increased in participants with obesity compared with the control group. Conversely, the expression of the SIRT1 gene in individuals with obesity was lower than that in control participants. A strong negative correlation was observed between miR‐141 and SIRT1 and a strong positive association was observed between miR‐141 and metabolic parameters. Furthermore, participants with fatty liver had significantly elevated levels of miR‐141 gene expression and lower expression of SIRT1 gene, compared to those without fatty liver. Conclusion elevated levels of miR‐141 in individuals with obesity might be a contributing factor in the repression of SIRT1 in obesity and its consequences, including NAFLD. Therefore, miR‐141 might serve as a suitable diagnostic and therapeutic target in obesity and NAFLD.